Growth and inequality in Ireland: 1987 - 1999 - Cathal Clancy; David Madden (University College Dublin, Department of Economics, 2005)
This paper analyses data from the Irish Household Budget Surveys of 1987, 1994 and 1999 to examine the evolution of inequality of income and expenditure over that period. The paper calculates Lorenz and Generalised Lorenz curves and also the Growth Incidence Curve of Ravallion and Chen to investigate the extent to which growth was “pro-poor”. The paper also examines the composition of changes in inequality of income over the period.
hdl:10197/776
Keywords: D31; D63; I31; 330; Growth; inequality; Lorenz; Generalised Lorenz; growth incidence curve